PERANAN TOTAL QUALITY MANAGEMENT DALAM MENINGKATKAN KEPUASAN KONSUMEN - Asrizal, Asrizal; Mukaram, Mukaram (POLITEKNIK NEGERI BANDUNG, 2016)
One of the characteristics that the resulting product quality is the emergence of consumer satisfaction. Customer satisfaction will be achieved when the product quality of an organization that is supported by the implementation of Total Quality Management (TQM). The purpose of this study is to determine the level of implementation of TQM at Sekolah Dasar Islam Terpadu Bina Insan Mulia, determine the level of customer satisfaction atSekolah Dasar Islam Terpadu Bina Insan Mulia, as well as to determine whether TQM affects customer satisfaction at Sekolah Dasar Islam Terpadu Bina Insan Mulia. This study used a saturated sample technique by using the entire population of 113 as the study sample. Based on the results of the research level of implementation of TQM at Sekolah Dasar Islam Terpadu Bina Insan Mulia already